2011
DOI: 10.1111/j.1399-0012.2011.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic complications following lung transplantation: 64‐MDCT findings

Abstract: The aim of this review is to present the wide spectrum of common and uncommon thoracic complications that can affect the lung after transplantation. These complications were analyzed using 64 multi-detector row helical CT (MDCT). Sixty-four MDCT techniques and parameters are illustrated. Correlations of imaging findings and pathologic and histologic specimens obtained by transbronchial biopsy and broncoalveolar lavage are illustrated in representative cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is also worth highlighting that some causes of diaphragmatic palsy were found to be avoidable, notably pull on the phrenic nerve, manipulation of the mediastinum, use of metallic retractors for the pericardium and injury to the pericardio-phrenic vasculature [ 9 , 35 – 38 , 42 , 45 , 46 ], with two studies observing a decrease in the occurrence of diaphragmatic palsy following the transition from retractor utilisation to suspension sutures or hand-retraction [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth highlighting that some causes of diaphragmatic palsy were found to be avoidable, notably pull on the phrenic nerve, manipulation of the mediastinum, use of metallic retractors for the pericardium and injury to the pericardio-phrenic vasculature [ 9 , 35 – 38 , 42 , 45 , 46 ], with two studies observing a decrease in the occurrence of diaphragmatic palsy following the transition from retractor utilisation to suspension sutures or hand-retraction [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermic nerve injury secondary to the application of ice has been identified in various reports. Additionally, pull on the phrenic nerve, manipulation of the mediastinum, use of metallic retractors for the pericardium and injury to the pericardio-phrenic vasculature has been implicated to various extents [ 9 , 19 , 35 – 38 , 42 46 ]. Only one study found no impact for using retraction instruments, or even traction of the diaphragm, on the incidence of diaphragmatic palsy [ 12 ].…”
Section: Surgical Factorsmentioning
confidence: 99%
See 1 more Smart Citation